2015
DOI: 10.1016/j.jpha.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro–in vivo studies of the quantitative effect of calcium, multivitamins and milk on single dose ciprofloxacin bioavailability

Abstract: Ciprofloxacin, commonly used in India as an anti-microbial for prolonged use in chronic and non-specific indications, may affect the bioavailability of the drug. The drug prescribed is commonly taken with multivitamins, calcium and milk. A simple and reliable analytical methodology obtaining a correlation with in vivo urinary excretion studies using UV and HPLC and in vitro dissolution studies (IVIVC) has shown a significant increase in elimination rate of ciprofloxacin co-administered with multivitamins, calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…Also ciprofloxacin graded doses alone showed antibacterial activity against all the test organisms. However, (22). The antagonistic action in our study may be also due to variation in the composition of camel milk which depends on the season, lactation period, feeding conditions, and water availability when compared to synergistic finding reported by Yassin 2015 (6).…”
Section: Discussionsupporting
confidence: 42%
“…Also ciprofloxacin graded doses alone showed antibacterial activity against all the test organisms. However, (22). The antagonistic action in our study may be also due to variation in the composition of camel milk which depends on the season, lactation period, feeding conditions, and water availability when compared to synergistic finding reported by Yassin 2015 (6).…”
Section: Discussionsupporting
confidence: 42%
“…Data analysis was performed by calculating percent release of sitagliptin when treated alone and in presence of different antacids using following formula (Dey et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…High-protein meals can enhance presystemic metabolism by inducing catabolic enzymes, which degrade oral-administrated bioactive compounds. 36,37 The solubility of lipophilic drugs is enhanced by fats contained in milk. 38 In this study, milk significantly reduced the AUC values of Cur-NE but showed no remarkable effects on the AUC values of Cur-SS, Cur-SWNT, and Cur-NLC.…”
Section: Discussionmentioning
confidence: 99%